Thioredoxin 2 Offers Protection against Mitochondrial Oxidative Stress in H9c2 Cells and against Myocardial Hypertrophy Induced by Hyperglycemia - Hong Li; Changqing Xu; Quanfeng Li; Xiu-xiang Gao; Erkio Sugano; Hiroshi Tomita; Liming Yang; Sa Shi (2017)
Mitochondrial oxidative stress is thought to be a key contributor towards the development of diabetic cardiomyopathy. Thioredoxin 2 (Trx2) is a mitochondrial antioxidant that, along with Trx reductase 2 (TrxR2) and peroxiredoxin 3 (Prx3), scavenges H2O2 and offers protection against oxidative stress. Our previous study showed that TrxR inhibitors resulted in Trx2 oxidation and increased ROS emission from mitochondria. In the present study, we observed that TrxR inhibition also impaired the contractile function of isolated heart. Our studies showed a decrease in the expression of Trx2 in the high glucose-treated H9c2 cardiac cells and myocardium of streptozotocin (STZ)-induced diabetic rats. Overexpression of Trx2 could significantly diminish high glucose-induced mitochondrial oxidative damage and improved ATP production in cultured H9c2 cells. Notably, Trx2 overexpression could suppress high glucose-induced atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) gene expression. Our studies suggest that high glucose-induced mitochondrial oxidative damage can be prevented by elevating Trx2 levels, thereby providing extensive protection to the diabetic heart.